2017
DOI: 10.1155/2017/8986165
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Sugarcane Vinasse into High-Added Value Products and Energy

Abstract: Vinasse, a residue from bioethanol production containing high organic matter concentration, was used as substrate in submerged fermentation of Pseudomonas aeruginosa PA1 for biosurfactant production. About 2.7 g/L of rhamnolipids was obtained, with surface tension of 29.2 mN/m and critical micelle concentration of 80.3 mg/L. After separation of rhamnolipid and biomass, residual fermentation media were submitted to anaerobic biodegradation in mesophilic conditions. The residual medium derived from fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 40 publications
1
22
0
5
Order By: Relevance
“…Sugarcane vinasse, a residue from bioethanol production is a common waste during fermentation using substrate from sugar crops. It also contains sugars and is able to serve as a substrate for rhamnolipids production [ 58 ]. Pseudomonas aeruginosa PA1 could produce 2.7 g/L of rhamnolipids when sugarcane vinasse was used as a substrate in submerged fermentation [ 58 ].…”
Section: Microbial Production Of Rhamnolipids Using Sugar-containingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugarcane vinasse, a residue from bioethanol production is a common waste during fermentation using substrate from sugar crops. It also contains sugars and is able to serve as a substrate for rhamnolipids production [ 58 ]. Pseudomonas aeruginosa PA1 could produce 2.7 g/L of rhamnolipids when sugarcane vinasse was used as a substrate in submerged fermentation [ 58 ].…”
Section: Microbial Production Of Rhamnolipids Using Sugar-containingmentioning
confidence: 99%
“…It also contains sugars and is able to serve as a substrate for rhamnolipids production [ 58 ]. Pseudomonas aeruginosa PA1 could produce 2.7 g/L of rhamnolipids when sugarcane vinasse was used as a substrate in submerged fermentation [ 58 ]. Pseudomonas luteola B17 and P. putida B12 grown on autoclaved medium consisting of sugarcane beet molasses mixed with distilled water, gave maximum rhamnolipids production at 72 h [ 59 ].…”
Section: Microbial Production Of Rhamnolipids Using Sugar-containingmentioning
confidence: 99%
See 1 more Smart Citation
“…cellulose by Acetobacter, chitosan by Mucorales, galactoglucopolysaccharides and biosurfactant by Achromobacter, Agrobacterium, Pseudomonas, Rhizobium and Zooglea, scleroglucan by Sclerotium, and welan by Alcaligenes [9][10][11]. Due to the wide diversity of structures and functional properties, there is an increasing interest in EPSs synthesized by microorganisms [12][13][14].…”
mentioning
confidence: 99%
“…If considered the discharge of vinasse in water bodies, a more catastrophic effect is expected, since vinasse is highly toxic to aquatic biota with a pollution potential hundred times higher than household sewage (Christofoletti et al, 2013 ). Naspolini et al ( 2017 ) have reported the rhamnolipid production by Pseudomonas aeruginosa PA1 from medium containing glycerol and sugarcane vinasse. Interestingly, these authors not only obtained a biosurfactant production but also they reported a 63.2% COD removal from culture medium.…”
Section: Resultsmentioning
confidence: 99%